2009
DOI: 10.1002/path.2554
|View full text |Cite
|
Sign up to set email alerts
|

The histone deacetylase inhibitor LBH589 inhibits expression of mitotic genes causing G2/M arrest and cell death in head and neck squamous cell carcinoma cell lines

Abstract: Head and neck squamous cell carcinoma represents a complex set of neoplasms arising in diverse anatomical locations. The site and stage of the cancer determine whether patients will be treated with single or multi-modality therapy. The HDAC inhibitor LBH589 is effective in treating some haematological neoplasms and shows promise for certain epithelial neoplasms. As with other human cancer cell lines, LBH589 causes up-regulation of p21, G2/M cell cycle arrest, and cell death of human HNSCC cell lines, as measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 193 publications
(220 reference statements)
2
35
0
Order By: Relevance
“…HBx also plays a role in regulating a series of cell-signaling cascades, most notably in the Ras-and Raf-induced mitogen-activated protein kinase pathways, and in inactivation of tumor suppressive genes through promoter hypermethylation (30). Previous studies have demonstrated that HBx deletion, especially the COOHterminal deletion of HBx, is a frequent event in HBV-associated HCC tissues (11,12,24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HBx also plays a role in regulating a series of cell-signaling cascades, most notably in the Ras-and Raf-induced mitogen-activated protein kinase pathways, and in inactivation of tumor suppressive genes through promoter hypermethylation (30). Previous studies have demonstrated that HBx deletion, especially the COOHterminal deletion of HBx, is a frequent event in HBV-associated HCC tissues (11,12,24).…”
Section: Discussionmentioning
confidence: 99%
“…Hepatitis B virus x protein (HBx), derived from hepadnavirus genomes, is a promiscuous transactivator, and it can cause aberrant expression of molecules involved in transcriptional regulation, signal transduction, cell cycle progress, protein degradation pathways, apoptosis, and genetic stability by directly or indirectly interacting with host factors (6)(7)(8). HBx deletion, especially the COOH-terminal deletion of HBx, was found in many HBV-infected HCC patients (9)(10)(11)(12). Previous findings showed that different domains of HBx-COOH might represent various functions, and that the mutants may directly affect the proliferation and invasion of HCC by regulating the cell cycle.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that DNA methylation level and global histone modification patterns may be possible predictors of cancer recurrence and prognosis in a large variety of cancer entities (5,6). Post-translational modification of histone tails alters the physical state of chromatin and has an essential role in both transcriptional repression and activation during embryonic development, lineage specification, terminal differHigh expression of trimethylated histone H3 at lysine 27 predicts better prognosis in non-small cell lung cancer XIAOHUI CHEN 1,4 , NING SONG entiation and tumorigenesis as well (7,8). One such repressive modification, the trimethylation of lysine 27 on histone H3 (H3K27me3), seemed to be an epigenetic label mediating gene silencing; and a mark for de novo DNA methylation in cancer cells by recruitment of DNA methyltransferase (DNMTs) (9)(10)(11), contributing to tumor progression through suppression of a certain gene expression (12).…”
Section: Introductionmentioning
confidence: 99%
“…28 Although demethylating agents have been used and approved for different hematological malignancies such as AML and myelodysplastic syndromes, 29 the experience in patients with ALL is very limited. 30 On the other hand, the HDACi and specifically LBH589 (Panobinostat) have demonstrated preclinical activity in vitro and in vivo in a wide range of malignancies, such as subcutaneous and Hodgkin lymphomas, 31 multiple myeloma, 19 melanomas, 32 lung cancer, 33 colon cancer cell lines, 34 head and neck squamous cell carcinoma, 35 glioma cells 36 and some hematological malignances. 37 Similarly, the number of studies using LBH589 in ALL is very limited.…”
Section: In Vitro Activity Of Lbh589 In All Cellsmentioning
confidence: 99%